Analisis Kesehatan Koperasi Simpan Pinjam Pembiayaan Syariah Surya Utama Nusantara Pada Masa Pandemi Covid-19 Tahun 2020 - Fanniar Rohman, Hilma; Rachmadina Marzani, Yaumi (Jurnal Etnik: Ekonomi-Teknik, 2022)
This research is based on the background of the Covid-19 pandemic in 2020 which has a negative impact on all aspects of life including the economy so that Indonesia's economic growth has contracted. The slow pace of economic growth affects the pace of economic activity, such as banking, cooperatives, both sharia and conventional. The financial institution that has experienced a decline in profitability is the KSPPS Surya Utama Nusantara. So in this study, the problem formulation and the research objective is to find out how the Health of the Surya Utama Nusantara Syariah Financing Savings and Loan Cooperative during the Covid-19 pandemic in 2020. The research method used in this research is quantitative descriptive using primary data and secondary data. . Primary data is obtained by collecting data through interviews and observations, while secondary data comes from the financial statements of KSPPS Surya Utama Nusantara. Measurement of the level of health of cooperatives according to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises Number: 06 / Per / Dep.6 / IV / 2016 can be carried out on 7 aspects, namely: 1) Capital Aspects. 2) Earning Asset Quality Aspects. 3) Management Aspects. 4) Efficiency Aspects. 5) Liquidity Aspects. 6) Aspects of Independence and Growth. 7) Aspects of cooperative identity.